2011
DOI: 10.1021/la2005024
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Binding Energy and Solubility Parameters for Functionalized Gold Nanoparticles by Molecular Dynamics Simulation

Abstract: The binding energy, density, and solubility of functionalized gold nanoparticles in a vacuum are computed using molecular dynamics simulations. Numerous parameters including surface coverage fraction, functional group (-CH(3), -OH, -NH(2)), and nanoparticle orientation are considered. The analysis includes computation of minimum interparticle binding distances and energies and an analysis of mechanisms that may contribute to changes in system potential energy. A number of interesting trends and results are obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
(57 reference statements)
0
16
0
Order By: Relevance
“…Both united atom [12][13][14][15][16][17][18][19][20] and atomistic force elds [21][22][23][24][25][26] have been used. Interactions and ligand structure between multiple NPs 18,19,28,29 have also been studied. These studies indicate that, for high ligand coverage, ligand order may be relevant for NP ligand behavior within a membrane at elevated temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Both united atom [12][13][14][15][16][17][18][19][20] and atomistic force elds [21][22][23][24][25][26] have been used. Interactions and ligand structure between multiple NPs 18,19,28,29 have also been studied. These studies indicate that, for high ligand coverage, ligand order may be relevant for NP ligand behavior within a membrane at elevated temperature.…”
Section: Introductionmentioning
confidence: 99%
“…They have also further extended their study to understand the effects of charged ligands on coating asymmetry 43 . Henz et al have concentrated on determining the binding energy, density and solubility parameters of functionalized gold nanoparticles in vacuum 44 .…”
Section: Introductionmentioning
confidence: 99%
“…Modeling a system with explicit presence of PVP structures adsorbed to NCs in presence of water using DFT approaches is not practical and hence MD simulations based on force fields are used to investigate this phenomenon ,. Previously, MD simulations have been used to obtain atomistic level details of NCs adsorbed to proteins, DNA, lipids and dendrimers ,. Most of these studies used Lennard‐Jones (LJ) potentials for the metal NCs, and this methodology was shown to reasonably reproduce the energetics and geometric features obtained using DFT methods .…”
Section: Introductionmentioning
confidence: 99%